O procedurze i skutkach wycofania zaświadczenia A1 raz jeszcze. Glosa do wyroku TSUE z 16 listopada 2023 r., C-422/22 - Lach, Daniel Eryk (Studia Prawa Publicznego, 2024)
ZUS’s withdrawal of the A1 certificate regarding an employee delegated to work in the EU resulted in practical problems related to including this employee in the appropriate social security system of the place of work. As a result, in its jurisprudence the Supreme Court formulated a controversial requirement to precede the withdrawal of the A1 certificate by ZUS by agreeing with the institution of the place of work on retroactive subjection to the applicable legislation. This position, which is assessed critically in the literature, was rejected by the Court of Justice of the EU in its judgment of November 16, 2023, C-422/22. The Court found that Articles 5, 6 and 16 of Regulation (EC) No 987/2009 must be interpreted as meaning that the institution that issued an A1 certificate which, following a review on its own initiative of the evidence on which the issue of that certificate is based, finds that evidence to be incorrect, may withdraw that certificate without first initiating the dialogue and conciliation procedure laid down in Article 76(6) of Regulation (EC) No 883/2004 with the competent institutions of the Member States concerned with a view to determining the national legislation applicable. The subject of the gloss is an approving discussion of this judgement.